The effects of pregnancy happiness on prenatal attachment and maternity function: a longitudinal study - Barut, Sumeyye; Kurt, Nuray; Baransel, Esra Sabanci (Assoc Medica Brasileira, 2025)
OBJECTIVE: The aim of the study was to investigate the relationship between pregnancy happiness and prenatal attachment, as well as postpartum maternal functioning. METHODS: The studywas conducted between December 2022 and January 2024 and involved 312 women. Data were collected using the Oxford Happiness Scale Short Form, Prenatal Attachment Inventory, and Barkin Maternity Function Scale. The Oxford Happiness Scale Short Form was administered during the second trimester of pregnancy, the Prenatal Attachment Inventory during the third trimester, and the Barkin Maternity Function Scale at 6-10 weeks postpartum. RESULTS: The study found that prenatal attachment mediates the effect of pregnancy happiness on maternal functioning. Additionally, it was observed that both pregnancy happiness and prenatal attachment have a direct impact on maternal functioning. CONCLUSION: This study clarifies the mechanism linking pregnancy happiness and maternal functioning. The findings suggest that increasing levels of pregnancy happiness and prenatal attachment may improve positive attitudes and ensure high maternal functioning.
Keywords: Pregnancy; Happiness; Motherhood; Maternal-fetal relations